Developmental Hurdles That Can Compromise Pregnancy during the First Month of Gestation in Cattle - Savannah L. Speckhart; Mary A. Oliver; Alan D. Ealy (Animals, 2023)
Several key developmental events are associated with early embryonic pregnancy losses in beef and dairy cows. These developmental problems are observed at a greater frequency in pregnancies generated from in-vitro-produced bovine embryos. This review describes critical problems that arise during oocyte maturation, fertilization, early embryonic development, compaction and blastulation, embryonic cell lineage specification, elongation, gastrulation, and placentation. Additionally, discussed are potential remediation strategies, but unfortunately, corrective actions are not available for several of the problems being discussed. Further research is needed to produce bovine embryos that have a greater likelihood of surviving to term.